An Analysis of Students' Errorneous Sentence Found in Descriptive Text Written by Students in Sintang - Sijono Sijono; Thomas Joni Verawanto Aristo (Universitas Hamzanwadi, 2019)
The problems of this research were the students tended to use the Indonesian language structure when translating. Besides, they wrote a false word order in their sentences and also misuse the tenses for the existing sentences. This research aimed to identify and describe the students’ errors in the form of interlingual errors and intralingual errors. The qualitative research design was used to analyze the data. There were 70 samples of students’ writing tasks which were taken from three state senior high schools and three private senior high schools in Sintang city. The finding showed the aspects that more influenced the learners made errors when transferring the first language to the target language were identified as two major aspects. The errors caused by the students’ first language are interlingual. While the errors caused by the structure of the target language are called intralingual errors. To identify the interlingual errors the researchers used two subcategories. They were the use of the L1 structure and the omission of BE form. The most error in interlingual errors was caused by the L1 structure. Meanwhile, the researchers used four subcategories to identify intralingual errors. They are overgeneralization, ignorance of rule restriction, incomplete application of rules and false concepts hypothesized. The most error in intralingual errors happened because of the learner’s limited knowledge of the target language. Based on these findings, Teachers can solve the problems by providing explicit and implicit corrective feedback, introducing the grammar system of both Indonesian and English when teaching grammar.